1983
DOI: 10.1002/eji.1830130607
|View full text |Cite
|
Sign up to set email alerts
|

Role of human factor I and C3b receptor in the cleavage of surface‐bound C3bi molecules

Abstract: Control of functions mediated by the third component of complement (C3) depends on the rate of generation and degradation of biologically active C3 fragments. To evaluate the mechanisms of degradation of active C3 fragments, the role of the control protein C3b/C4b inactivator (factor I) was investigated under conditions approximating those found in vivo, i.e. in the presence of plasma. The breakdown of human erythrocyte-bound C3bi molecules in serum or plasma was mediated only by factor I, since factor I-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 29 publications
0
37
0
2
Order By: Relevance
“…3), in agreement with in vitro studies in which pretreating PBL with anti-Mac-l (27) On normal cells, anti-Mo 1, anti-Mac-I or anti-OKM10 effectively blocked C3bi receptor-depedent rosette formation suggesting that Mol/Mac-l/OKMl are closely associated (3,4) or identical (28) with the C3bi receptor. It has also been suggested that EAC43bi can bind to the C3b receptor (29,30,31 Structural studies revealed that the patient's cells were deficient in the two subunits of Mol antigen (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…3), in agreement with in vitro studies in which pretreating PBL with anti-Mac-l (27) On normal cells, anti-Mo 1, anti-Mac-I or anti-OKM10 effectively blocked C3bi receptor-depedent rosette formation suggesting that Mol/Mac-l/OKMl are closely associated (3,4) or identical (28) with the C3bi receptor. It has also been suggested that EAC43bi can bind to the C3b receptor (29,30,31 Structural studies revealed that the patient's cells were deficient in the two subunits of Mol antigen (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…Factor I is a serine protease that cleaves C3b at its serine residues, yielding a specific cleavage pattern (14,26). The C3b cleavage assay employed here was previously employed by McDowell and colleagues to demonstrate the complement regulatory activity of factor H bound to the relapsing fever spirochetes B. hermsii and Borrelia parkeri and the Lyme disease spirochete, B. burgdorferi (23).…”
Section: Fig 5 Demonstration Of Fhl-1-independentmentioning
confidence: 99%
“…CR1 appears to endow these cells with the capacity to clear circulating immune complexes (CIC)' by transporting them to the liver where they are removed by local macrophages (8,9). In addition, CR1 acts as cofactor of factor I in the inactivation of C3b and C4b (2,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%